The Role of the Police in Combating Motor Vehicle Theft within the Jurisdiction of the Bengkulu Regional Police - Zhoffi Mahari P Siagian; Muhammad Citra Ramadhan; Wenggede Frensh (Journal of Public Representative and Society Provision, 2026)
This research aims to analyze the mitigation of motor vehicle theft crimes (curanmor) within the jurisdiction of the Bengkulu Regional Police (Polda Bengkulu), focusing on the role of the police, the challenges faced, and the solutions implemented. This study employs a field research method with a descriptive case study approach, involving data collection through observation, in-depth interviews, and document analysis. The research was conducted at Polda Bengkulu, specifically at the Directorate of General Criminal Investigation (Ditreskrimum), from March to July 2024. The informants consisted of 4 Ditreskrimum investigators, 1 member of Polda Bengkulu, and 2 members of the community. The results indicate that motor vehicle theft, particularly motorcycles, is a prevalent crime in Bengkulu, with increasingly organized modus operandi and extensive networks. The main factors driving the high rate of motorcycle theft include weak vehicle security systems, economic factors, and high market demand for used motorcycle parts. The Bengkulu Regional Police have undertaken various preventive measures, such as increasing routine patrols, night raids, joint operations, and the use of technology like CCTV. Additionally, public education on the importance of using additional security devices and parking in safe locations is also part of the prevention strategy. The conclusion of this research is that addressing vehicle theft requires a comprehensive approach involving primary, secondary, and tertiary prevention. Primary prevention can be achieved through improved access to education and employment opportunities, while secondary prevention involves routine patrols and the use of technology. Tertiary prevention focuses on the rehabilitation and reintegration of former offenders into society. Synergy between the police, government, and the community is key to reducing vehicle theft crime rates and creating a safer environment.